Using basic research as a catalyst to exploit new technology-based innovations-a case study - Hameri, Ari-Pekka (Technovation)
The difficulties related to the commercialization, or even to the introduction, of new technologies and solutions to common problems are well documented. The paper presents a case on how to introduce new technology to a complex research environment, in order to catalyse its commercialization. The central theme of the approach is on understanding all the possible applications and implications that the new technology shares when implemented to replace conventional solutions. The potential customer of the new technology and the related technological domains must be mapped systematically to establish technological trajectories which overlap with the possible applications. This mapping provides the framework for detailed application analysis with pointers to the right people responsible for the potential application area.